Ecology and parasitism of the lizard Tropidurus jaguaribanus (Squamata: Tropiduridae) from northeastern Brazil - Alcantara, Edna P. [UNESP]; Ferreira-Silva, Cristiana [UNESP]; Sousa, José Guilherme G.; Ávila, Robson W.; Morais, Drausio H. (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2018)
Specimens of Tropidurus jaguaribanus were collected as part of a study of their use of microhabitats, activity period, body temperature, diet, foraging, sexual dimorphism (in size and in form), reproductive biology, and parasite community composition. The preferential microhabitat of the species is the surface of rocks (saxicolous habit). The species has a bimodal diurnal activity period and a seasonal reproductive cycle. The diet is composed mainly of beetles and ants in adults and juveniles. The species is a sit-and-wait forager; the lizards scarcely move and feed on sedentary, immobile prey. The helminth community associated with these lizards is composed of five species: Oochoristica travassosi, Parapharyngodon alvarengai, Physaloptera sp., Spauligodon sp., and Strongyluris oscari. The prevalence, intensity of infection, and parasite abundance is the same in both sexes.
Keywords: Diet; Foraging; Habitat; Parasites; Reproduction